If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(n + 8) = 8 + -3n Reorder the terms: -1(8 + n) = 8 + -3n (8 * -1 + n * -1) = 8 + -3n (-8 + -1n) = 8 + -3n Solving -8 + -1n = 8 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. -8 + -1n + 3n = 8 + -3n + 3n Combine like terms: -1n + 3n = 2n -8 + 2n = 8 + -3n + 3n Combine like terms: -3n + 3n = 0 -8 + 2n = 8 + 0 -8 + 2n = 8 Add '8' to each side of the equation. -8 + 8 + 2n = 8 + 8 Combine like terms: -8 + 8 = 0 0 + 2n = 8 + 8 2n = 8 + 8 Combine like terms: 8 + 8 = 16 2n = 16 Divide each side by '2'. n = 8 Simplifying n = 8
| 6x=21+7y | | 0.5*x+x=4.5 | | 4(y+2)=34 | | (4/9)^1/2 | | 0.5*x=4.5 | | 15c-6=8c+78 | | y=-7/2x | | 7(2x-5)=6x-11 | | -14f+14f=-10 | | -10a=-71 | | -16-6=v | | 3/5_____=300 | | 6a^4b^-3c^2/-10ab^6c^7 | | -8z(2z+3z^2+3z^3)= | | -12-3p=-6p-3p | | 3x-12=5x-26 | | 20c=30 | | 60.00=0.14x+29.95 | | (5)√(32/1024) | | n-(-2)+7=22 | | 5y+x-6=0 | | 5(2a-6)-3(4a-7)= | | 48=6ysquared | | -5-7k=-4k+4 | | 48x^2-3=13 | | 7-7(6x+6)=133 | | 6y+x=4y+-x | | 3(-6)+2(12)= | | 14-2x/4x=20 | | 45p=-108 | | -(2-r)+10r= | | 19(1000-4.26y)+81y=19000 |